2007
DOI: 10.1007/s10856-007-3172-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone-like matrix formation on magnesium and magnesium alloys

Abstract: Mg metal and its alloys have promise as a biocompatible, degradable biomaterials. This work evaluates the potential of in vitro cell culture work with osteoblast-like cells on Mg based materials, and investigates cell differentiation and growth on Mg alloyed with various non-toxic or low-toxicity elements. Mg based substrates support the adhesion, differentiation and growth of stromal cells towards an osteoblast-like phenotype with the subsequent production of a bone like matrix under in vitro conditions. No s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 29 publications
3
71
1
Order By: Relevance
“…Osteoinductive properties, which were observed for magnesium implants in previous in vitro [14] and in vivo studies with magnesium implant materials [15,11,19] , could not be confirmed in the present study. Although calcium phosphate precipitates were already found on the surface of magnesium after two weeks of implantation; which corresponds to an in vitro study, in which calcium phosphate precipitates were described on pure magnesium surface in synthetic biological media [20] , chondromatosis or cellular bone structures could not be observed even after an implantation period of 32 weeks.…”
Section: Magnesium Implants Induced Minor Tissue Responses In Contrascontrasting
confidence: 99%
“…Osteoinductive properties, which were observed for magnesium implants in previous in vitro [14] and in vivo studies with magnesium implant materials [15,11,19] , could not be confirmed in the present study. Although calcium phosphate precipitates were already found on the surface of magnesium after two weeks of implantation; which corresponds to an in vitro study, in which calcium phosphate precipitates were described on pure magnesium surface in synthetic biological media [20] , chondromatosis or cellular bone structures could not be observed even after an implantation period of 32 weeks.…”
Section: Magnesium Implants Induced Minor Tissue Responses In Contrascontrasting
confidence: 99%
“…Pietak et al reported very similar total protein synthesis and alkaline phosphatase activity in comparison with the glass control when rat bone marrow derived stromal cells were directly cultured on the Mg sample (99.8% purity) and the glass control for 8 days. 35 However, it is impossible to compare these results and draw a meaningful conclusion at this stage because of the significant variations in the surface, purity, and dimension of Mg samples as well as the cells used and the methods of cell culture and detection. To reduce the use of laboratory animals and speed up the new alloy development and screening, it is definitely necessary to develop standardized in vitro tests and establish models that can predict in vivo performance based on in vitro data.…”
Section: In Vitro Degradation Of Magnesiummentioning
confidence: 99%
“…Adding 9% Al to a Mg-Zn alloy yields the AZ91 alloy that has a higher corrosion resistance than Al-free Mg alloys and pure Mg [6][7][8], probably owing to the ÎČ-Mg 17 Al 12 phase. However, Mg alloys with relatively high Al content suppress cell growth on their surface [9].…”
Section: Introductionmentioning
confidence: 99%